A Computer Simulation of Hubble Telescope Including Eyepiece Nano- Sensors to Increase Optical Efficiency - Alaa B. Hasan (Pakistan Journal of Medical & Health Sciences, 2023)
The Hubble telescope is characterized by the accuracy of the image formed in it, as a result of the fact that the surrounding environment is free of optical pollutants. Such as atmospheric gases and dust, in addition to light pollution emanating from industrial and natural light sources on the earth’s surface. The Hubble telescope has a relatively large objective lens that provides appropriate light to enter the telescope to get a good image. Because of the nature of astronomical observation, which requires sufficient light intensity emanating from celestial objects (galaxies, stars, planets, etc.). The Hubble telescope is classified as type of the Cassegrain reflecting telescopes, which gives it the advantage of eliminating chromatic aberration. Zemax optical design program was used to simulate the design of the Hubble telescope with nanosensors eyepiece, and to evaluate its performance through a set of analysis tools in the program, by changing some of the optical parameters that affect the performance of the telescope. The results proved needing of the imaging optical system (telescope) to align the observed object to avoid off-axial aberration. When the angle of incidence of the rays is changed to an appropriate extent, the image is negatively affected as a result of the increase in the amounts of aberration in it. The simulation also showed the similarity of the optical parameters that are related to the engineering design to get the best picture, through the analysis tools used in the program. Keywords: Reflective telescope, Nano sensors, Hubble, optical efficiency, Zemax program.